Systematic review of the efficacy of parenting interventions for children with cerebral palsy - Whittingham, K.; Wee, D.; Boyd, Roslyn (2011)
This systematic review aims to evaluate the efficacy of parenting interventions (i.e. behavioural family intervention and parent training) with parents of children with cerebral palsy (CP) on child behavioural outcomes and parenting style/skill outcomes. The following databases were searched: Medline (1950-April 2010), PubMed (1951-April 2010), PsycINFO (1840-April 2010), CINAHL (1982-April 2010) and Web of Science (1900-April 2010). No randomized clinical trials of parenting interventions with parents of children with CP were identified. Three studies were identified that involved the examination of a targeted parenting intervention via a pre-post design. Interventions utilized included the implementation of parenting interventions in conjunction with behavioural intervention and oral motor exercises for children with CP and feeding difficulties, the Hanen It Takes Two to Talk programme and a Functional Communication Training programme for parents. All studies found changes in relevant child behavioural outcomes. The studies reviewed suggest that parenting interventions may be an effective intervention for parents of children with CP. However, the current research is limited to pre-post designs of targeted parenting interventions (e.g. parenting interventions focused upon communication). A randomized controlled trial of parenting interventions for families of children with CP is urgently needed to address this paucity in the literature and provide families of children with CP with an evidence-based intervention to address child behavioural and emotional problems as well as parenting challenges. © 2011 Blackwell Publishing Ltd.